Molecular epidemiology, antimicrobial resistance, and virulence characteristics of predominant methicillin-resistant Staphylococcus aureus clones with strong biofilm-producing capability from a tertiary teaching hospital in China - Minghui Hao; Junrui Wang (BMC Microbiology)
Abstract Background Methicillin-resistant Staphylococcus aureus (MRSA) is one of the most prevalent bacterial pathogens leading to various kinds of infections, but the characteristics of this superbug with both strong biofilm-producing and intracellular invasive capabilities is rarely reported. This study aimed to investigate the genotypic and phenotypic features of this superbug with above two properties. Methods Phenotypic resistance profiling of MRSA clinical isolates was performed via the VITEK 2 AST-GP67 Test Kit. Biofilm production was assessed via crystal violet staining and the Congo red agar (CRA) method. The biofilm-degrading activity was tested using Proteinase K, Dispersin B, and DNase I. The intracellular invasive capability was evaluated via dilution plate count and immunofluorescence assay. Genotyping was performed using multilocus sequence typing and staphylococcal protein A typing methods, and virulence genes were detected via polymerase chain reaction. Flow cytometry was performed to assess the cytotoxicity of the dominant MRSA clones. Results A high prevalence (21.6%) of MRSA isolates exhibiting strong biofilm-forming capability was observed in this study, including 70 strains with the highest level of biofilm production (optical density > 0.4). DNase I exhibited the most effective biofilm-degrading activity, with the biofilm-degrading percentage of 78.6% of the strains exceeding 50%. Simultaneously, 71.4% of the isolates exhibited strong invasive capability into A549 cells. ST5-t2460 (48.6%), ST59-t437 (20%), and ST239-t030 (11.4%) were identified as the predominant clones. In particular, ST5-t2460 and ST239-t030 clones exhibited broader antibiotic resistance to gentamicin, ciprofloxacin, levofloxacin, moxifloxacin, and tetracycline compared with ST59-t437 clone. In addition, a higher percentage of the isolates belonging to ST5-t2460 (91.2%) and ST239-t030 (100%) clones demonstrated stronger intracellular invasive capability relative to those belonging to ST59-t437 clone (14.3%). Furthermore, ST5-t2460 and ST239-t030 clones displayed stronger cytotoxicity and carried higher proportions of adhesion-related genes (fnbA, sdrD, sasC) and other virulence genes (sea, seb, sec, isdB, lukE-D, tsst-1). Conclusions This is the first report of the phenotypic–genotypic characteristics of MRSA with both strong biofilm-producing and virulence potential, with ST5-t2460, ST59-t437, and ST239-t030 clones accounting for the major genotypes. Further exploration of specific virulence genes correlating to the pathogenesis of this superbug is deemed essential for developing targeted infection control and treatment strategies in the future.